2013
DOI: 10.1111/ped.12157
|View full text |Cite
|
Sign up to set email alerts
|

Micafungin versus fluconazole for prophylaxis against fungal infections in premature infants

Abstract: MCFG was superior to FLCZ as prophylaxis against fungal infections in extremely low-birthweight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This recommendation is due to the prevalent fluconazole resistance of C. auris [ 21 , 34 ]. A small comparative clinical study reported that micafungin compared to fluconazole prophylaxis against fungal infections in extremely low-birthweight infants was associated with a decreased incidence of C. albicans infections [ 146 ]. Additionally, safety and pharmacokinetics of micafungin were previously assessed in very low birthweight infants [ 147 , 148 , 149 ].…”
Section: C Auris Antifungal Resistance and Therapeutic Optionsmentioning
confidence: 99%
“…This recommendation is due to the prevalent fluconazole resistance of C. auris [ 21 , 34 ]. A small comparative clinical study reported that micafungin compared to fluconazole prophylaxis against fungal infections in extremely low-birthweight infants was associated with a decreased incidence of C. albicans infections [ 146 ]. Additionally, safety and pharmacokinetics of micafungin were previously assessed in very low birthweight infants [ 147 , 148 , 149 ].…”
Section: C Auris Antifungal Resistance and Therapeutic Optionsmentioning
confidence: 99%
“…Comparison of single dose pharmacokinetic studies in adult, paediatric, and infant patient populations reported micafungin clearance in premature infants >1000 g to be much higher compared to older children and adults. Micafungin has been used in premature infants for prophylaxis against C. albicans and was found to be superior to fluconazole 12–14 . Our protocol for prophylaxis was to administer micafungin at a dose of 3 mg/kg/day intravenously daily for infants under 32 weeks of gestation as had been reported 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Micafungin has been used in premature infants for prophylaxis against C. albicans and was found to be superior to fluconazole. [12][13][14] Our protocol for prophylaxis was to administer micafungin at a dose of 3 mg/kg/day intravenously daily for infants under 32 weeks of gestation as had been reported. 14 This was given for the first 2 weeks after birth or longer till central lines were removed.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…This suggestion comes as a result of the high resistance that C. auris momentarily presents to fluconazole [ 32 , 87 ]. A small, comparative clinical study reported that the use of micafungin, in comparison to fluconazole, for prophylaxis against fungal infections in ELBW neonates was connected with lower rates of C. albicans infection [ 88 ]. Furthermore, the safety and pharmacokinetics of micafungin have been evaluated in VLBW [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%